2020
DOI: 10.3390/buildings10090152
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-Mechanical Properties of a Wood Fiber Insulation Board Using a Bio-Based Adhesive as a Binder

Abstract: The goal of the present study was to develop a low-density thermal insulation board using wood fibers and a bio-based adhesive as a binder, which was prepared from a crude glycerol and citric acid mixture. The physical and mechanical properties of insulation boards manufactured using two ratios of crude glycerol and citric acid (1:0.66 and 1:1 mol/mol) and two adhesive contents (14% and 20%) were evaluated. The results show that the insulation boards with a range of density between 332 to 338 kg m−3 present th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 25 publications
1
14
0
1
Order By: Relevance
“…So far, only marginal efforts have been made to investigate natural adhesives for the production of wood fiber insulation boards to produce more natural and sustainable products. Examples in this context are enzymatic activation of wood fibers [ 7 , 8 , 9 ], protein adhesive based on blood albumin [ 10 ] or an adhesive based on crude glycerol and citric acid [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…So far, only marginal efforts have been made to investigate natural adhesives for the production of wood fiber insulation boards to produce more natural and sustainable products. Examples in this context are enzymatic activation of wood fibers [ 7 , 8 , 9 ], protein adhesive based on blood albumin [ 10 ] or an adhesive based on crude glycerol and citric acid [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The production processes of the building materials significantly increase the carbon footprint of buildings, also due to high energy consumption. The application of natural, renewable, sustainable, and environmentally friendly materials such as wood or agricultural byproducts significantly reduces the amount of waste materials and environmental pollution [ 1 , 2 , 3 , 4 ]. The most popular natural building materials are wood and annual plants being used as structural and/or insulation materials.…”
Section: Introductionmentioning
confidence: 99%
“…Bio-based materials have recently become popular in the building and construction industry due to their insulation and hygroscopic properties [ 10 , 11 ]. Studies have reported that using these materials in construction increases the energy efficiency of the building and provide a comfortable and healthy indoor environment [ 12 , 13 , 14 ]. Some bio-based materials also have the ability to absorb and release moisture with respect to changing relative humidity levels, which can reduce the load on air conditioning and have a positive impact on wellbeing of residents [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%